Chronic Hepatitis C: Treatment Comparison Between 3 and 5 Million Units of Interferon Alpha-2b - Castro, Fernando; Torres, Esther A.; Oharriz, Juan; González-Keelan, Carmen; Pérez, Cynthia; Rubio, Carlos (Puerto Rico Health Sciences Journal, 2016)
see manuscript